AUTOMATIC LIGHT DESIGN USING PHOTODIODE SENSORS AND ARDUINO UNO - Alfaridwan; Astriany Rizky, Ardelia (INFOKOM (Informatika & Komputer), 2025)
This study aims to design an automatic light control system utilizing a photodiode sensor, Arduino Uno, relay module, lamp, jumper wires, and a breadboard. The device operates based on the intensity of ambient light. The photodiode sensor detects changes in light, which are then processed by the Arduino Uno microcontroller to activate or deactivate the lamp via the relay module. When the environment is detected as dark, the light will automatically turn on, and it will turn off when sufficient light is detected. This device does not require motion detection but still provides energy efficiency and user convenience. Test results show that the system functions accurately and is responsive to changes in light intensity, making it suitable for application in various spaces such as bedrooms, hallways, and outdoor areas.